Layer-by-layer technique to developing functional nanolaminate films with antifungal activity - Fabra, María José (2016)
The layer-by-layer (LbL) deposition method was used to build up alternating layers (five) of different polyelectrolyte solutions (alginate, zein-carvacrol nanocapsules, chitosan and chitosan-carvacrol emulsions) on an aminolysed/charged polyethylene terephthalate (A/C PET) film. These nanolaminated films were characterised by contact angle measurements and through the determination of water vapour (WVTR) and oxygen (O2TR) transmission rates. The effect of active nanolaminated films against the Alternaria sp. and Rhizopus stolonifer was also evaluated. This procedure allowed developing optically transparent nanolaminated films with tuneable water vapour and gas properties and antifungal activity. The water and oxygen transmission rate values for the multilayer films were lower than those previously reported for the neat alginate or chitosan films. The presence of carvacrol and zein nanocapsules significantly decreased the water transmission rate (up to 40 %) of the nanolaminated films. However, the O2TR behaved differently and was only improved (up to 45 %) when carvacrol was encapsulated, i.e. nanolaminated films prepared by alternating alginate with nanocapsules of zein-carvacrol layers showed better oxygen barrier properties than those prepared as an emulsion of chitosan and carvacrol. These films containing zein-carvacrol nanocapsules also showed the highest antifungal activity (30 %), which did not significantly differ from those obtained with the highest amount of carvacrol, probably due to the controlled release of the active agent (carvacrol) from the zein-carvacrol nanocapsules. Thus, this work shows that nanolaminated films prepared with alternating layers of alginate and zein-carvacrol nanocapsules can be considered to improve the shelf-life of foodstuffs.